Ambient seismic vibrations in steep bedrock permafrost used to infer variations of ice-fill in fractures - Weber, Samuel; id_orcid:0 000-0003-0720-5378; Fäh, Donat; Beutel, Jan; id_orcid:0 000-0003-0879-2455; Faillettaz, Jérome; Gruber, Stephan; Vieli, Andreas (Earth and Planetary Science Letters, 2018)
ISSN:0012-821X ISSN:1385-013X